2010
DOI: 10.1093/nar/gkq195
|View full text |Cite
|
Sign up to set email alerts
|

Rad52 SUMOylation affects the efficiency of the DNA repair

Abstract: Homologous recombination (HR) plays a vital role in DNA metabolic processes including meiosis, DNA repair, DNA replication and rDNA homeostasis. HR defects can lead to pathological outcomes, including genetic diseases and cancer. Recent studies suggest that the post-translational modification by the small ubiquitin-like modifier (SUMO) protein plays an important role in mitotic and meiotic recombination. However, the precise role of SUMOylation during recombination is still unclear. Here, we characterize the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 37 publications
4
81
0
Order By: Relevance
“…The assay was performed as described, with some modifications [50]. Purified Aos1/Uba2 (400 nM), Ubc9 (2.8 μM), Smt3 (5.6 μM), 2.5 mM ATP, buffer S (50 mM HEPES, 10 MgCl 2 , 0.1 mM DTT) and 5.6 μM of various Rad59 proteins were mixed in a 10 μl reaction volume and incubated at 4 °C for 1 h. In the indicated cases, 50 nM Siz1 or 50 nM Siz2 were added to the mixture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The assay was performed as described, with some modifications [50]. Purified Aos1/Uba2 (400 nM), Ubc9 (2.8 μM), Smt3 (5.6 μM), 2.5 mM ATP, buffer S (50 mM HEPES, 10 MgCl 2 , 0.1 mM DTT) and 5.6 μM of various Rad59 proteins were mixed in a 10 μl reaction volume and incubated at 4 °C for 1 h. In the indicated cases, 50 nM Siz1 or 50 nM Siz2 were added to the mixture.…”
Section: Methodsmentioning
confidence: 99%
“…The relevance of these SUMO modifications in regulating HR remains mostly unclear, but in some instances it has been possible to demonstrate a direct role of SUMOylation in regulating protein–protein interactions, protein localization or activity [41]. In particular, SUMOylation of Rad52 at lysines 43, 44 and 253 (using the original amino acid numbering [48] or lysines 10, 11 and 220 when considering the first actual start codon [49]) is induced by DNA damage and shields the protein from proteasomal degradation [44], inhibits its DNA binding and strand annealing activities [50], and inhibits Rad52-mediated recombination within the nucleolus [51]. Important for our understanding of these effects, SUMOylated proteins can be recognized and bound non-covalently by other proteins through a SUMO-interacting motif (SIM) as reported for Srs2 and SUMOylated PCNA, and for Rad51 and SUMOylated Rad52 [46,5254].…”
Section: Introductionmentioning
confidence: 99%
“…In brief, the 10 μl reaction contained 150 nM Aos1/Uba2, 0.5 μM Ubc9, 4.3 μM Smt3 or Smt3-KR, 0.4 μM Rad1-Rad10, 1 mM adenosine triphosphate (ATP) and buffer S1 (100 mM Tris-HCl pH 7.5, 10 mM MgCl 2 ) (53). In the indicated cases, 10–100 nM Siz1 or 10–100 nM Siz2 was added to the reaction.…”
Section: Methodsmentioning
confidence: 99%
“…For Rad52, it was shown that sumoylation on lysines 43, 44, and 253 inhibits its ssDNA binding and annealing activities without affecting its interaction with Rad51 and RPA (Altmannova et al 2010), and sumoylation of Rad52 protects it from proteasomal degradation (Sacher et al 2006). Moreover, stimulating Rad52 sumoylation by overexpression of the Siz2 SUMO ligase or by fusing SUMO to the C terminus of Rad52 suppressed the DNA damage sensitivity of srs2 cells (Esta et al 2013).…”
Section: Regulation Of Homologous Recombinationmentioning
confidence: 99%